Kesinambungan dan Kesamaan Agama - Burhan Djamaluddin; Muhammad Yasin (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
The research is to show the continuity of teachings that are in line with human values and identify similarities in basic values between religions that can strengthen relations between religious believers in a multicultural society, then to explain aspects of continuity in religious teachings and identify similarities in basic values between religions to support harmony in multicultural life. This research uses the library research method, an approach that relies on collecting and analysing data from various relevant written sources. The purpose of this research is to explore and understand the continuity and similarity of basic values between religions and their implications in building harmony in a multicultural society. The research also succeeded in identifying similarities in basic inter-religious values, such as compassion, justice, generosity, and respect for differences, which are important foundations for strengthening relations between religious believers in a multicultural society. Through a literature review, this research shows that the continuity in the teachings of the major religions lies in their cross-cultural and interfaith messages of peace, harmony and humanity. These aspects include the encouragement to live in togetherness, cooperation in goodness, and mutual respect in the midst of diversity. The commonality of basic values between religions provides a solid foundation for building harmony.